Digitalization of Learning and the Fragility of Elementary School Students' Character in Kecamatan Rongga: A Case Study of Deep Learning from the Perspectives of Kohlberg and Freud - Via Nurafiati Astuti; Ace Suryadi; Mupid Hidayat; Imas Kurniawaty (Dinasti Publisher, 2026)
Digitalization within the framework of New Pedagogies for Deep Learning (NPDL) is ideally expected to foster future-ready character competencies. However, realities in educational settings reveal a technological paradox. This qualitative case study aims to explore the manifestations of character degradation among elementary school students resulting from passive digitalization and to formulate strategies for its reconstruction. Employing John W. Creswell’s bounded system case study design, the research was conducted over a two-month period in elementary schools under the supervision of Rongga District, West Bandung Regency, Indonesia. Data were collected through participant observation, in-depth interviews with school principals and teachers, and curriculum document analysis. The findings confirm a widespread fragility in students’ character foundations, characterized by declining discipline, reduced learning focus in classrooms, and the strengthening of individualistic and egocentric attitudes. From the psychoanalytic perspective of Sigmund Freud, excessive dependence on digital devices gratifies students’ Id, causing the Ego to fail in regulating learning focus and self-control. Meanwhile, according to Lawrence Kohlberg’s theory of moral development, children's moral orientation remains trapped at the pre-conventional level, where self-interest predominates, thereby undermining social intelligence and moral responsibility.As a solution, this study proposes character reconstruction through transforming technology from a passive entertainment medium into a structured active-learning instrument that educates and strengthens students’ Ego. This approach is integrated with teachers’ pedagogical role modeling and the consistent cultivation of digital ethics. It is concluded that the wise and purposeful use of technology in schools can restore the essence of deep learning while simultaneously revitalizing the social and moral functions of students in the era of artificial intelligence.